Sex estimation from measurements of the calcaneus: Applications for personal identification in Thailand - Shelby Scott (2018)
© 2017 Elsevier B.V. As a coastal region, Thailand has been significantly affected by climate change. The impacts of climate change in Thailand – temperature increase, rising sea levels, and violent flooding – are predicted to multiply in both frequency and intensity in the next few decades, which may cause an increase in mass disasters and fatalities in the region. The 2004 tsunami catastrophe in Thailand demonstrated the lack of forensic anthropology expertise and the lack of population specific methods in the region. The goal of this research is to derive population specific discriminant functions from the calcaneus for sexing unidentified skeletal remains from a contemporary Thai population. Nine variables of the calcaneus were measured from 232 individuals (116 males and 116 females) of the Chiang Mai skeletal collection with age ranges from 22 to 96 years. All nine calcanei variables were sexually dimorphic. Multivariate and univariate discriminant function analyses were completed. The multivariate analyses showed accuracy rates from 81.5% to 87.7% in males and 84.0% to 87.7% in females. The accuracy rates from the univariate analyses ranged from 71.6% to 84.0% in males and 67.9% to 85.2% in females. Comparisons to other populations were made and the results demonstrated the need for population specific discriminant functions. Overall, the cross-validation accuracies ranged from 73.4% to 94.3% with males identified correctly more often than females. This study demonstrates that the calcaneus is useful for sex estimation in the contemporary Thai population.